Identification and Analysis of Long Non-Coding RNAs Related to UV-B-Induced Anthocyanin Biosynthesis During Blood-Fleshed Peach (Prunus persica) Ripening - Zhang, Man; Zhang, Xiuqi; Wang, Haijing; Ye, Mao; Liu, Yating; Song, Zhihua; Du, Tingting; Cao, Hongyan; Song, Liqin; Xiao, Xiao; Liu, Jianzhen; Zhang, Libin; et al. (Frontiers in Genetics, 2022)
Blood-flesh is a key fruit trait in peaches (Prunus persica) and can be attributed to the accumulation of anthocyanins. Multiple studies have highlighted the roles of long non-coding RNAs (lncRNAs) in regulating fruit ripening, anthocyanin accumulation, and abiotic stress responses in many flowering plants. However, such regulatory roles of lncRNAs in Prunus persica have not been reported. In this study, we sequenced and analyzed the complete transcriptome of C3-20 (a blood-fleshed peach) fruit at four developmental stages. Analyses of the differentially expressed lncRNA target genes and correlated genes helped predict the potential roles of lncRNAs. The RNA-seq data was generated using high-throughput sequencing. In total, 17,456 putative lncRNAs, including 4,800 intergenic lncRNAs, 2,199 antisense lncRNAs, and 10,439 intronic lncRNAs, were identified, of which 4,871 differentially expressed lncRNAs (DE-lncRNAs) were annotated in the fruit developmental processes. We also predicted the target genes of these DE-lncRNAs and their regulatory relationship (cis- or trans-acting) that identified 21,795 cis-regulated and 18,271 trans-regulated targets of the DE-lncRNAs. The enriched GO terms for the target genes included anthocyanin biosynthesis. The enriched KEGG pathways also included plant hormone signal transduction and flavonoid biosynthesis. Co-expression network construction showed that the highly expressed genes might co-regulate multiple other genes associated with auxin signal transduction and act in the same pathways. We identified lncRNAs (LNC_000987, LNC_000693, LNC_001323, LNC_003610, LNC_001263, and LNC_003380) that were correlated with fruit ripening and the climacteric and may participate in the regulation of ethylene biosynthesis and metabolism and the ABA signaling pathway. Several crucial transcription factors, such as ERFs, WRKY70, NAC56, and NAC72, may also regulate fruit ripening. Three DE-lncRNAs, XLOC_011933, XLOC_001865, and XLOC_042291, are involved in UV-B-induced anthocyanin biosynthesis and positively regulating UVR8 and COP10, were identified and characterized. Our discovery and characterization of XLOC_011933, XLOC_001865, and XLOC_042291 provide a more precise understanding and preliminarily establishes a theoretical framework for UV-B-induced flesh anthocyanin biosynthesis. This phenomenon might encourage more in-depth investigations to study the molecular mechanisms underlying peach flesh coloring.